HiPIMS co-sputtering for the increase of the mechanical properties of arc deposited TiN coatings - Chi-Lung Chang; Kuo-Chun Lo; Fu-Chi Yang; Guan-Lun Shen; Jian-Fu Tang (Journal of Materials Research and Technology, 2023)
Relatively few studies have addressed the use of vacuum arc evaporation (VAE) in conjunction with high-power impulse magnetron sputtering (HiPIMS), due to differences in the respective pressure requirements. This paper describes the use of HiPIMS-enhanced VAE (HEVAE) technology for the deposition of TiN coatings on tungsten carbide and silicon wafers. We determined that HiPIMS could reduce the formation of macro-particle (MP) defects, while enhancing hardness and adhesion strength. Electron microscopy results revealed that both the quantity and size of MPs decreased inversely with HiPIMS power. Under the highest HiPMS power (4 kW), we observed a notable decrease in the size of columnar crystals and a significant increase in the number of nanocrystalline structures. The formation of nanocrystals enhanced hardness by reducing the probability of dislocations. Overall, HiPIMS power of 4 kW proved optimal in terms of MP formation, hardness (32.1 GPa), and adhesion strength (137 N).